Biophysical characterization of p53 core domain aggregates. Issue 1 (8th January 2020) - Lima, Igor; Navalkar, Ambuja; Maji, Samir K.; Silva, Jerson L.; de Oliveira, Guilherme A.P.; Cino, Elio A.
Abstract : Aggregation is the cause of numerous protein conformation diseases. A common facet of these maladies is the transition of a protein from its functional native state into higher order forms, such as oligomers and amyloid fibrils. p53 is an essential tumor suppressor that is prone to such conformational transitions, resulting in its compromised ability to avert cancer. This work explores the biophysical properties of early-, mid-, and late-stage p53 core domain (p53C) aggregates. Atomistic and coarse-grained molecular dynamics (MD) simulations suggest that early- and mid-stage p53C aggregates have a polymorphic topology of antiparallel and parallel β-sheets that localize to the core amyloidogenic sequence. Both topologies involve similar extents of interstrand mainchain hydrogen bonding, while sidechain interactions could play a role in regulating strand orientation. The free energy difference between the antiparallel and parallel states was within statistical uncertainty. Negative stain electron microscopy of mature fibrils shows a wide distribution of fiber widths, indicating that polymorphism may extend to the quaternary structure level. Circular dichroism of the fibrils was indicative of β-sheet rich structures in atypical conformations. The Raman spectrum of aggregated p53C was consistent with a mixture of arranged β-sheets and heterogeneous structural elements, which is compatible with the MD findings of an ordered β-sheet nucleus flanked by disordered structure. Structural polymorphism is a common property of amyloids; however, because certain polymorphs of the same protein can be more harmful than others, going forward it will be pertinent to establish correlations between p53C aggregate structure and pathology.